Analisis Faktor-Faktor Yang Mempengaruhi Sikap Pengelolaan Keuangan Pada Mahasiswa Manajemen Universitas PGRI Semarang - Rizky Agung Nugroho; Rita Meiriyanti; Heri Prabowo (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This study aims to determine the influence of financial knowledge, locus of control and financial attitudes towards financial management on Management Students of PGRI Semarang University Class of 2018-2021. This type of research uses quantitative research methods and the data used in this study are primary data. The population in this study is Management Students of PGRI University Semarang, this study uses the Probability Sampling technique with a sample of 299 respondents. The measurement of this study used a Likert scale which was then processed with the IBM SPSS Statistical Version 25 analysis tool using multiple linear analysis. The results of this study show that there is a positive and significant influence between financial knowledge (X1) and financial management (Y) partially, locus of control (X2) has a positive and significant effect on financial management (Y) partially, financial attitude (X3) has a positive and significant effect on financial management (Y) partially. Financial knowledge, locus of control, financial attitudes have a shared influence on financial management simultaneously. The results of the coefficient of determination (R2) test obtained a value from Ajusted R Square of 0.235 or 23.5% showed that financial management variables were influenced by financial knowledge variables, locus of control, financial attitudes, while the remaining 76.5% were influenced by other variables that were not in this study.